(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2025)
This article presents a brief review of the exploration of identity in select early Nepali paintings and literary texts. Rather than providing a comprehensive analysis of the entire artistic and literary oeuvre, it focuses on identifying key trends. Portraiture is highlighted as a primary medium through which this theme is studied. The broader subject of identity has long engaged the attention of scholars and art critics worldwide. This article serves as a modest reflection on that ongoing discourse, presenting it as a topic of both research and discussion. In the Nepali context, we observe that painters have frequently employed portraiture to express identity, often working in close collaboration with literary writers. The available examples suggest a notable harmony between visual art and literature. A particularly striking case is that of the first Rana Prime Minister, Jang Bahadur, who strategically used both painting and literary text to construct and amplify his public persona. This article examines such interact practices, highlighting the creative intersections between artists and writers. Having written on related aspects of this subject in earlier issues of SIRJANĀ, in this article I have chosen to focus more specifically on the patterns and examples of portraiture in Nepali art and literary texts from the same historical period.